Influence of organic soil on the mycoliactericidal activity of the commercial sodium hypochlorite with 2.5% of active chlorine - Guerrero, Andrea Castillo; Pinheiro, Sonia Regina; Morais, Zenáide Maria de; Vasconcellos, Silvio Arruda; Ito, Eumio Honma; Ferreira Neto, José Soares (Brazilian Journal of Veterinary Research and Animal Science, 1993)
It was evaluated the highest working dilution of the sodium hypochlorite solution (available as household and laundry bleach, with 2.5% of active chlorine) still effective in inactivating Mycobacterium fortuitum in the presence of different levels of bovine feces as organic soil. The experiments were conducted "in vitro" using filter paper as carriers. The time of contact was one hour at the temperature range of 4 to 8°C. The blocking of the desinfectant activity was achieved by the dilution using a solution of 0.5% sodium thiosulphate with 0.05% twenn-80 (v/v). The remaining microrganisms were cultivated in Lowenstcin-Jensen culture medium and the number of colonies forming unities was statiscally evaluated by the MannWhitneyTest. The results showed that the organic soil affected the desinfectant activity. The working dilutions calculated were 1:64 and 1:16, respectively, with and without organic soil. In working dilutions higher than 1:64 the regularity of the desinfectant action was very poor.